Study and Estimation of Hardness of Water by pH-Metric Titration Method - Abhijit Mallick (Chemistry and Biochemistry: Research Progress Vol. 5, 2025)
The hardness of water is one of the most important parameters of water quality. The hardness of water arises primarily due to the presence of a profuse amount of Ca2+ and Mg2+ ions in the natural water resources. The complexometric titration method is a prevalent technique in estimating the concentrations of Ca2+ and Mg2+ and ions individually, which are primarily responsible for the hardness of water. However, the method needs two external indicators to mark the endpoints of titrations. Furthermore, accuracy of the method is sacrificed due to inevitable parallax errors during marking of the endpoint of titration. This present work proposes a novel technique to estimate the concentrations of Ca2+ and Mg2+ ions of a given water sample. Two different hard water samples are prepared to estimate the hardness of water by pH-Metric Titration Method. This present work reports that during titration of a hard water sample with a complexing agent (here, Na2 EDTA solution), pH changes continuously. This change in pH is closely monitored and recorded graphically. The recorded data reveals two distinct linear regions with significantly different slopes, indicating the titration endpoint. The neutralization volume, thus obtained, is used to estimate Ca- and Mg- hardness of the water sample separately. This novel technique obviates the use of any external indicators and eliminates any possible parallax error. Besides conventional spectroscopic and volumetric titration methods, this novel method is believed to be useful to monitor other chemical reactions accurately, exploring future research works. This pH- metric study is expected to have potential in the development of analytical chemistry and chemical processes related to industry.